FEATURES OF THE HISTORICAL ANALYSIS OF THE DEVELOPMENT OF SOCIETY - Vaulin Vladimir Ivanovich (JURNAL HISTORICA, 2025)
The purpose of the study is to systematize the methodology of historical knowledge of the development of society. In the course of the research, the diachronic method and method of generalizations of the historical stages of the formation of the methodology of historical cognition were used. A special chronological method for the development of methodology stages. Historical-systematic method of systematization of methodological approaches to the study of history, the function of historical knowledge, methods of historical cognition. The method of content analysis of historiography sources. The study used universal methods of analyzing and summarizing the opinions of scientists during the discussion of the problem of the mythology of the Tarar-Mongol yoke in Russia. The article analyzes methodological approaches to the study of the history of science. Their formation is considered in the historical chronology. The stages of methodology formation with the main ideas of their founders are considered. The article highlights the basic principles and functions of historical knowledge. Methods of historical cognition are systematized. The main sources of historical knowledge formation are revealed. It is argued that scientific historical knowledge has the properties of objectivity, systematization, verification, concreteness of knowledge of the historical process of development of society or their totality. It is concluded that historical science creates prerequisites for predicting the development options of a particular society, the formation of a positive social consciousness, the management of the development process of society and its individual spheres. The systematization of the methodology of history allows us to consider the formation of the theoretical basis of scientific knowledge of history. It is advisable to exclude the mythologization of historical events and personalities in history in the context of a negative interpretation.